O fenômeno informacional indígena na contemporaneidade - Mello, Rodrigo Piquet Saboia de (2019)
The theme of this research is the information produced about and by indigenous peoples themselves. This doctoral thesis conducts a study about the entitled indigenous information phenomenon, a new concept created in this academic course. Through the historical context of the confrontations that the indigenous peoples experienced in history until the memory and the subject knowledge were reached, the present work produces an investigation of how natives, previously left behind of the hegemonic information centers, emerged and began to reinvent practices, technologies and processes of documentation. It was possible to glimpse the route covered by documentation of ethnological nature: at first, a series of documents was produced by the Brazilian State with the objective of controlling and monitoring areas where indigenous peoples lived; already in a second moment, the indigenous peoples acquire an informational autonomy, by means of the constitution of its own centers of documentation. It is also important to remember the importance of the constitution of indigenous assemblies during the Brazilian Military Dictatorship and the movement for the claim and emancipation of indigenous peoples, headed by indigenous Xavánte Mário Juruna. In the meantime, UNESCO's documentation projects are being implemented in a web of negotiation involving actors such as the third sector, universities, international organizations, the Brazilian State and the indigenous peoples themselves. The information in this scenario is reappropriated by the indigenous peoples, who transform it into an instrument of struggle for better living conditions, such as the guarantee of indigenous lands. Finally, it is possible to affirm that the indigenous information phenomenon is a unique emergency in the present historical context and that the management of the new information and communication technologies, the promotion of indigenous documentation centers and a greater democratization of the indigenous repositories under the Brazilian State represent a positive path for the ethnic reassertion of indigenous peoples, as well as for the democratic advancement of Brazilian society.